Comparative Analysis of Operational Structures in Single- and Dual-Mode Distance Learning Institutions in Nigeria - Olatunji, Taiwo Isaac; Adewumi Adebisi, Tajudeen (International Review of Research in Open and Distributed Learning, 2021)
This study examined the similarities and differences in the processes and facilities for distance education at National Open University of Nigeria (NOUN), a single-mode distance learning institution, and Obafemi Awolowo University (OAU), Ile-Ife, a dual-mode distance learning institution. The study adopted a case study research design, with a population of administrators/facilitators and distance learning students at both NOUN and OAU. The sample for the study consisted of 38 key informants (30 administrators/facilitators and 8 students) selected using a purposive sampling technique. All the administrators/facilitators responded to a key informant questionnaire; 8 of the administrators/facilitators and all 8 students were also interviewed. The 16 interviewees were selected based on gender, institution, educational role, and mode of distance learning. The collected data were analysed using tabular juxtaposition and phenomenological analysis techniques. Results showed that similarities in the operational structures at NOUN and OAU included the use of blended learning approaches. Differences in operations included compulsory tutorial attendance at OAU and the deployment of part-time and quasi part-time facilitators at NOUN and OAU, respectively. The study recommended an increase in the use of information and communications technology (ICT).